2019
DOI: 10.1016/j.ihj.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of resting and adenosine-free pressure indices with adenosine-induced hyperemic fractional flow reserve in intermediate coronary lesions

Abstract: ObjectiveFractional flow reserve (FFR) using adenosine has been the gold standard in the functional assessment of intermediate coronary stenoses in the catheterization laboratory. We aim to study the correlation of adenosine-free indices such as whole cycle Pd/Pa [the ratio of mean distal coronary pressure (Pd) to the mean pressure observed in the aorta (Pa)], instantaneous wave-free ratio (iFR), and contrast-induced submaximal hyperemia (cFFR) with FFR.MethodsThis multicenter, prospective, observational study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Por esse motivo, utilizaram-se figuras autoexplicativas e pouca descrição textual, buscando-se ilustrações sobre manifestações clínicas e sinais de deterioração precoce da condição clínica, a fim de que o leitor se identifique com elas e possa utilizá-las para mostrar aos cuidadores e profissionais da saúde como tem se sentido (Navidian, et al, 2015;Wingham, et al, 2015;Kessing, et al, 2014;Liu, et al, 2014;Wu, et al, 2017;Li & Shun, 2016;Chang, et al, 2017;Motal, Pimenta & Fitch, 2009). Além disso, a maioria dos pacientes também pode apresentar comprometimento cognitivo, cuja possível causa é a hipoperfusão cerebral (Raja, et al, 2019). Sendo assim, optou-se por priorizar ilustrações e linguagem simples e clara, que fossem de fácil compreensão.…”
Section: Resultsunclassified
“…Por esse motivo, utilizaram-se figuras autoexplicativas e pouca descrição textual, buscando-se ilustrações sobre manifestações clínicas e sinais de deterioração precoce da condição clínica, a fim de que o leitor se identifique com elas e possa utilizá-las para mostrar aos cuidadores e profissionais da saúde como tem se sentido (Navidian, et al, 2015;Wingham, et al, 2015;Kessing, et al, 2014;Liu, et al, 2014;Wu, et al, 2017;Li & Shun, 2016;Chang, et al, 2017;Motal, Pimenta & Fitch, 2009). Além disso, a maioria dos pacientes também pode apresentar comprometimento cognitivo, cuja possível causa é a hipoperfusão cerebral (Raja, et al, 2019). Sendo assim, optou-se por priorizar ilustrações e linguagem simples e clara, que fossem de fácil compreensão.…”
Section: Resultsunclassified
“…In another study, Alfredo Fede et al [28] included more than 50 patients with borderline lesions and there was close agreement between the FFR and the IFR (R = 0.83, P < 0.0001). Deep Chandh Raja et al [29] found that IFR correlated with FFR in all the subgroups and across all the vessels, without any influence for the heart rate or blood pressure on the correlation with FFR. Also, there are some meta-analysis studies that addressed this point and clarified this concordance.…”
Section: Median 60mentioning
confidence: 95%
“…However, further validation is needed for adenosine-free indices to be commonly used in clinical practice. [34] Cost-effectiveness of FFR…”
Section: Clinical Evidence Related To the Benefits Of Ffr In Cadmentioning
confidence: 99%